Highly efficient poly(acrylic acid-co-aniline) grafted itaconic acid hydrogel: Application in water retention and adsorption of rhodamine B dye for a sustainable environment - GÜNDÜZ, OĞUZHAN (My University, 2022)
© 2022 The AuthorsThe present study used a free radical co-polymerization approach to synthesize a smart hydrogel of itaconic acid grafted poly(acrylic acid-co-aniline) (ItA-g-poly(AA-co-ANi)). ItA-g-poly(AA-co-ANi) hydrogel was characterized by Fourier transform infrared spectroscopy (FT-IR), Raman, X-ray diffraction (XRD), thermogravimetric analysis (TGA), field emission scanning electron microscope (FE-SEM), and X-ray photoelectron spectroscopy (XPS) analysis. Rhodamine B (RhB) dye was removed from an aqueous medium using ItA-g-poly(AA-co-ANi) hydrogel. To determine the maximum adsorption, the effect of parameters such as initial dye concentration, contact time, pH, and adsorbent dose were examined. The ItA-g-poly(AA-co-ANi) hydrogel had a high swelling percentage of 1755.3%. The high water penetration of ItA-g-poly(AA-co-ANi) hydrogel with a high swelling rate exposed the internal adsorption sites for RhB dye adsorption. The adsorption performance of ItA-g-poly(AA-co-ANi) hydrogel was explained by the pseudo-first-order and Freundlich adsorption isotherm models. Moreover, after four adsorption-desorption cycles, the ItA-g-poly(AA-co-ANi) hydrogel maintained an adsorption efficiency of 85.2%. The high water retention ability of ItA-g-poly(AA-co-ANi) hydrogel improved the moisture maintenance limit of soil for irrigation up to 23 days. As a result, ItA-g-poly(AA-co-ANi) hydrogel can be used in the elimination of toxic dyes as well as in irrigation systems.
Keywords: Sağlık Bilimleri; Eczacılık; Meslek Bilimleri; Farmasötik Toksikoloji; Sosyal ve Beşeri Bilimler; Sosyoloji; Yaşam Bilimleri; Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Health Sciences; Pharmacology and Therapeutics; Professional Sciences; Pharmaceutical Toxicology; Social Sciences and Humanities; Sociology; Life Sciences; Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); Sosyal Bilimler (SOC); Mühendislik; Farmakoloji ve Toksikoloji; Sosyal Bilimler Genel; MÜHENDİSLİK, ÇEVRE; TOKSİKOLOJİ; KAMU, ÇEVRE VE İŞ SAĞLIĞI; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); Life Sciences (LIFE); Social Sciences (SOC); ENGINEERING; CHEMISTRY; PHARMACOLOGY & TOXICOLOGY; SOCIAL SCIENCES, GENERAL; ENGINEERING, ENVIRONMENTAL; TOXICOLOGY; PUBLIC, ENVIRONMENTAL & OCCUPATIONAL HEALTH; Çevre Mühendisliği; Fizik Bilimleri; Genel Kimya; Çevre Kimyası; Kirlilik; Halk, Çevre ve İş Sağlığı; Sağlık, Toksikoloji ve Mutajenez; Environmental Engineering; Physical Sciences; General Chemistry; Environmental Chemistry; Pollution; Public Health, Environmental and Occupational Health; Health, Toxicology and Mutagenesis; Itaconic acid; Hydrogel; Swelling; Rhodamine B dye; Adsorption; Water retention; METHYLENE-BLUE; KAPPA-CARRAGEENAN; SUPERABSORBENT; REMOVAL; CHITOSAN; WASTE; RAMAN; POLYMERIZATION; NANOCOMPOSITE; PURIFICATION